Gender, work and ethnic ideology: castellorizian Greeks in Perth, Australia - Chryssanthopoulou, Vassiliki (The Greek Review of Social Research, 2003)
This article analyses the values and practices surrounding work among the Castellorizian migrants of Perth, Western Australia. The article compares and analyses the occupational and class patterns of the Castellorizians of Perth and those of their original community on the island of Castellorizo, to focus upon the construction of Castellorizian ethnic identity. Castellorizian men, with an occupational background in business and the professions, selectively deploy elements of regional Castellorizian tradition and of Greek ethnic ideology, to emphasize their material success in Perth. Castellorizian women, on the other hand, stress the need to abstain from paid labour, while their children are young, and motherhood as a channel for the socialization of their children into Greek culture. This case study demonstrates that the Castellorizian elite of Perth hegemonically defines the historically grounded and gendered ethnic ideology that underlies Castellorizian ethnic identity. This ideology is open and inclusive and incorporates the predominant values and practices of the surrounding Australian society.